Labor supply and the demand for child care: an intertemporal approach - Junichi Minagawa; Thorsten Upmann (Center for Economic Studies and ifo Institute (CESifo), 2006)
In this paper, we present a model of a one parent one child household where parental decisions on labor supply, leisure, and the demand for private and public child care are simultaneously endogenized and intertemporally determined. We characterize the path of the optimal decisions and investigate the impact of various public child care fees and of the quality of public child care services on the parent's time allocation and the child's performance level. Our results show that different public child care policies may induce substantially diverging effects, and reveal that each policy frequently faces a trade off between an encouragement of labor supply and an enhancement of the child's performance.
Keywords: D91; H24; H42; J13; J22; 330